Neural Network Aided Computation of Generalized Spatial Modulation Capacity - Anxo Tato; Carlos Mosquera; Pol Henarejos; Ana Pérez-Neira (27th European Signal Processing Conference (EUSIPCO), 2019)
Generalized Spatial Modulation (GSM) is being considered for future high-capacity and energy efficient terrestrial networks. A variant such as Polarized Modulation (PMod) has also a role in Dual Polarization Mobile Satellite Systems. The implementation of adaptive GSM systems requires fast methods to evaluate the channel dependent GSM capacity, which amounts to solve multi-dimensional integrals without closed-form solutions. For this purpose, we propose the use of a Multilayer Feedforward Neural Network and an associated feature selection algorithm. The resulting method is highly accurate and with much lower complexity than alternative numerical methods.
Keywords: Generalized Spatial Modulation; Index Modulations; Machine Learning; Multilayer Feedforward Neural Network; Polarized Modulation

Channel dependent Mutual Information in Index Modulations - Pol Henarejos; Ana Pérez-Neira; Anxo Tato; Carlos Mosquera (ICCASP, IEEE International Conference on Acoustics, Speech, and Signal Processing, 2018)
Mutual Information is the metric that is used to perform link adaptation, which allows to achieve rates near capacity. The computation of adaptive transmission modes is achieved by employing the mapping between the Signal to Noise Ratio and the Mutual Information. Due to the high complexity of the computation of the Mutual Information, this process is performed off-line via Monte Carlo simulations, whose results are stored in look-up tables. However, in Index Modulations, such as Spatial Modulation or Polarized Modulation, this is not feasible since the constellation and the Mutual Information are channel dependent and it would require to compute this metric at each time instant if the channel is time varying. In this paper, we propose different approximations in order to obtain a simple closed-form expression that allows to compute the Mutual Information at each time instant and thus, making feasible the link adaptation.

Practical Implementation of Link Adaptation with Dual Polarized Modulation (Best paper award) - Anxo Tato; Carlos Mosquera; Pol Henarejos; Ana Pérez-Neira (11th International Symposium on Communication Systems, Networks, and Digital Signal Processing., 2018)

Link Adaptation Algorithms for Dual Polarization Mobile Satellite Systems - Anxo Tato; Pol Henarejos; Carlos Mosquera; Ana Pérez-Neira (9th EAI International Conference on Wireless and Satellite Systems, WISATS, 2017)
The use of dual polarization in mobile satellite systems is very promising as a means for increasing the transmission capacity. In this paper a system which uses simultaneously two orthogonal polarizations in order to communicate with the users is studied. The application of MIMO signal processing techniques along with Adaptive Coding and Modulation in the forward link can provide remarkable throughput gains up to 100 % when compared with the single polarization system. The gateway is allowed to vary the MIMO and Modulation  and Coding Schemes for each frame. The selection is done by means of a link adaptation algorithm which uses a tunable margin to achieve a predefined target Frame Error Rate.

Advanced Signal Processing Techniques for Fixed and Mobile Satellite Communications - Pol Henarejos; Ana Pérez-Neira; Nicolò Mazzali; Carlos Mosquera (8th Advanced Satellite Multimedia Systems Conference 14th Signal Processing for Space Communications Workshop, 2016)
Keywords: compass; full duplex; satcom

Performance study of multiuser interference mitigation schemes for hybrid broadband multibeam satellite architectures - Arnau, Jesus; Bertrand Devillers; C. Mosquera; Ana Pérez-Neira (EURASIP Journal on Wireless Communications and Networking, 2012)

Hybrid Space-Ground Processing for High-Capacity Multi-beam Satellite Systems - Arnau, Jesus; Michael Bergmann; Enzo Alberto Candreva; Giovanni Emanuele Corazza; Riccardo De Gaudenzi; Bertrand Devillers; Wilfried Gappmair; Francesco Lombardo; C. Mosquera; Ana Pérez-Neira; Ilaria Thibault; Alessandro Vanelli-Coralli (IEEE GLOBECOM, 2011)
Selected Areas in Communications Symposium - Satellite & Space Communications Track (GC'11 - SAC - SSC)